(3GdbjGOI hGdQbGHI hGdGJUGd GdEOGQjs - (3eYf eMehO(B, (3YjGUQIs; (3Hfj CMeO(B, (3eQhGf eMeOs ((3YeGf(B:s (3OGQ GdMGeO ddfTQ hGdJhRjY,s, 2015)
(3jJfGhd eONd Edi Yde GdGOGQI, GdhXGFa GdGOGQjI, GdQbGHI GdGOGQjI, GdeSGAdI, GdJbhje, GJNGP GdbQGQGJ, GdbjGOI GdEOGQjI, GdGJUGds
(3HHdjhZQGajG(B: 183-188s
Keywords: (3GdGJUGds; (3GdbjGOI GdEOGQjIs